2020
DOI: 10.5539/jps.v9n1p34
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plant Species Used to Treat Tonsillitis in Ethiopia: A Systematic Review

Abstract: In various areas of Ethiopia, different plant species have been reported having a medicinal role for ailment tonsillitis. However, the ethnomedicinal information on those medicinal plant species that cure the ailment is not summarized in a way that gives general information and initiates further study. Therefore, the objective of this review paper was to summarize the ethnomedicinal information about medicinal plant species that used to treat tonsillitis in Ethiopia. The result of the review indicated that her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This study is consistent with studies conducted by Worku [ 12 ] and Yirgu et al [ 18 ] who reported that herbs were the most dominant plant growth forms as well as used as remedies in the Ethiopian traditional medicine. The highest use of herbaceous plants as compared to other growth forms could be due to their accessibility, the higher possibility of obtaining pharmacologically active compounds, and the sociocultural beliefs and practices of the healers in treating the ailment [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study is consistent with studies conducted by Worku [ 12 ] and Yirgu et al [ 18 ] who reported that herbs were the most dominant plant growth forms as well as used as remedies in the Ethiopian traditional medicine. The highest use of herbaceous plants as compared to other growth forms could be due to their accessibility, the higher possibility of obtaining pharmacologically active compounds, and the sociocultural beliefs and practices of the healers in treating the ailment [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers and the natural health product sector have paid close attention to natural antibacterial agents as replacement of synthetic analogues. As a result, new natural antibacterial drugs produced from plants have been tested against a variety of infectious microorganisms (Sandip et al, 2021;Abebe et al, 2020). Turmeric (Curcuma longa L.) is a member of the Zingiberaceae family, which could be located in the tropics of Asia, Africa, and Australia.…”
Section: Introductionmentioning
confidence: 99%